28 June : Sarajevo 1914-Versailles 1919 : the war and peace that made the modern world - Sharp, Alan, 1943- (Haus histories.)
On June 28, 1919, the Peace Treaty was signed in the Hall of Mirrors at Versailles, five years to the day after the assassination of Archduke Franz Ferdinand in Sarajevo triggered Europe's precipitous descent into war. This war was the first conflict to be fought on a global scale. By its end in 1918, four empires had collapsed, and their minority populations, which had never before existed as independent entities, were encouraged to seek self-determination and nationhood. Following on from Haus's monumental thirty-two Volume series on the signatories of the Versailles peace treaty, The Makers of the Modern World, 28 June looks in greater depth at the smaller nations that are often ignored in general histories, and in doing so seeks to understand the conflict from a global perspective, asking not only how each of the signatories came to join the conflict but also giving an overview of the long-term consequences of their having done so.--Provided by publisher.